MODERNIOJI LAISVĖ IR LYGYBĖ KAIP DEMOKRATINIS VARTOJIMO PROJEKTAS. - Dzežulskis-Duonys, Eligijus (Problems / Problemos, 2014)
This paper discusses the philosophical hypothesis, which claims that modem democratic culture based on individual consumption and culturally stressed consumerism functions as an almost purely economic phenomenon. It is proposed to treat this culture as the mythical validation of goals of eternal freedom and equality, finding a way of pooling modem people together and at the same time being a contradictory form of their management and control. The article ends with the conclusions about the necessity of searching for other ways to convincingly justify and normatively legitimise the practical implementation of egalitarian and libertarian cultural and political theories, especially trying to establish them as a norm throughout the entire world.